Avaliação de linhagens de trigo do programa de melhoramento da UTFPR em ensaio de Valor de Cultivo e Uso (VCU) - Quadra, Felipe Chade de (2023)
Wheat (Triticum aestivum L.) is a globally significant cereal due to its socioeconomic and nutritional relevance. However, wheat production in Brazil still does not meet domestic demand, resulting in substantial imports. One of the main challenges in increasing national wheat production is the specific adaptation of cultivars to the different regions of the country. In this context, the Wheat Improvement Program at UTFPR (Federal Technological University of Paraná) seeks to develop wheat genotypes adapted to the conditions of Southwest Paraná and West Santa Catarina. This study aimed to select more productive wheat lines adapted to these regions through Cultivation Value and Use (VCU) trials. The experiments were conducted in Pato Branco-PR and Clevelândia-PR, representing the VCU I and II regions. The experiment used a randomized block design with three replications, with units composed of six wheat rows 5 meters long and spaced 0.20 meters apart, totaling 6 square meters. 11 lines developed by UTFPR in the first year of VCU were evaluated, along with 4 control varieties. Sowing took place between June and July, with base fertilizer and sowing density of 350 seeds per square meter, following recommended practices. Parameters such as grain yield, hectoliter weight and thousand seed weight were evaluated. Statistical analysis revealed significant interactions between genotypes and environments, indicating the importance of local adaptation. Genotypes such as UTF25 and UTFT170588 stood out, which showed high grain yield and stability. Furthermore, UTFT190147 showed a high hectoliter weight. These genotypes have the potential to contribute significantly to wheat production in the regions studied, if promising results are confirmed in the next evaluation cycles.